Plantar Tissue Characteristics in People With Diabetes With and Without Peripheral Neuropathy: A Novel Explanatory Model for DPN Risk Assessment - Yiming Li; Wei Wu; Liyun Xue; Tianyu Zhao; Yucheng Lu; Xiaohui Qiao; Hong Ding (Journal of Diabetes)
ABSTRACT Objectives Diabetic peripheral neuropathy (DPN) may affect the biomechanical properties and morphology of the plantar tissue. This study aimed to compare plantar stiffness and thickness in individuals with diabetes with and without DPN and develop a novel explanatory model for DPN risk assessment by integrating these measures with clinical parameters. Materials & Methods Thirty‐two healthy controls and 84 people with diabetes (41 with DPN and 43 without DPN) were included. Shear wave elastography evaluated plantar thickness and stiffness at the heel, hallux, and first and fifth metatarsal heads (1st MTH, 5th MTH). An integrated thickness or stiffness index was generated at multiple locations by principal component analysis (PCA). Results People with DPN showed a significant increase in plantar thickness (heel, 1st MTH) (p < 0.001) and stiffness (all tested locations) compared to healthy controls (p < 0.05). Moreover, plantar thickness at 1st MTH, plantar stiffness at 5th MTH, and integrated stiffness index generated by PCA were significantly higher in DPN than in the non‐DPN group (p < 0.05). A DPN explanatory model was developed using multivariate logistic regression, incorporating the integrated plantar stiffness index, diabetes duration, and gender. The model showed high discriminative ability (AUROC: 97.7%), with an optimal cutoff of 0.56 yielding 92.7% sensitivity and 95.3% specificity. Conclusion The integrated plantar stiffness index, combined with gender and diabetes duration, offers a novel approach for DPN, providing a noninvasive tool for DPN risk assessment.